Implementasi Bimbingan Pastoral Konseling Kristen Sebagai Panduan Anak Muda Kristen Dalam Hal Berpacaran - Makawimbang, Aisye; Tadung, Frieska Putrima; Andries, Amelia Inriani Andries; Wangka, Windasari; Tatuil, Teovani; Maringka, Praysi Kharisona; Maarisit, Alfrinda; Djodjobo, Triona Arini; Maperipe, Kezia Irene; Karinda, Inggrit Claudia; Mananeke, Meylani Putri; Edwin Hiwoi; Argeliano Ferdinandus Tawaris; Brian Hadi Mayore; Sri Wahyuni Coleng; Apni Mitje Aomol (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Romantic relationships in the Christian context emphasize the importance of the introduction period as special preparation for marriage. Dating here is not just an ordinary introduction, but is a preparatory stage that involves special attitudes and deep interactions. The formation of a relationship between two individuals of the opposite sex is an important stage on the road to marriage. Romantic relationships involve the understanding that humans are social creatures who need relationships with other people. Ideally, these relationships are developed after a person has gone through the youth period in understanding the difference between individual needs in a group and needs in personal relationships.